O przebaczeniu indywidualnym i kolektywnym. Refleksja filozoficzna - Kania, Witold (Śląskie Studia Historyczno-Teologiczne, 2023)
In the last decades, a topic of forgiveness has gained great importance on a social level. The work of Truth and Reconciliation Committee and apologies offered by political and religious leaders are representative signs of “collective forgiveness”. In this paper, I show first the object and essence of forgiveness using Hildebrand’s distinction between disvalue and objective evil for a person. I explain from the perspective of a harmful relationship between two individuals what forgiveness is not. Then I show conditions which should be fulfilled to forgive and to receive forgiveness. An analysis of individual forgiveness gives us a proper tool to understand the collective one. I argue that in a strict sense we can not talk about collective forgiveness. It is better to speak about the process of social, religious or political reconciliation. This process leads to “purification of memory” and builds up new relationships between two feuding groups. A healed past gives hope for a good future.